Ionic hydrogenation-directed stereoselective construction of C-20(H) stereogenic center in steroid side chains: Scope and limitations - Shingate, Bapurao B.; Hazra, Braja G. (Tetrahedron, 2017)
Stereoselective synthesis of steroidal C-20 tertiary alcohols with n-butyl, vinyl, furyl, thienyl, thiazolyl, aryl and pyridyl side chains via Grignard reaction or organolithium reagents have been realized starting from readily available 16-dehydropregnenolone acetate. The ionic hydrogenation of steroidal C-20 tertiary alcohols having furyl, methylfuryl, thienyl, phenyl and 4-methoxyphenyl side chains, resulted into the deoxygenated product with C-20 natural configuration in excellent yields. However, the alkyl, thiazolyl and pyridyl incorporated steroidal C-20 tertiary alcohols were failed under the same reaction condition. The scope of ionic hydrogenation is further highlighted through the stereoselective reduction of steroidal C-20,21-ene compounds with furyl, thienyl and 4-methoxyphenyl side chains gave the saturated compounds with C-20 natural configuration